Changing Weather-World in Nepal Himalaya: Exploring from Anecdotal Narratives - Poudel, Jiban Mani (Geographical Journal of Nepal, 2025)
As key agents in knowledge production in the local contexts,lived experiences of local people serve as evidence and data. This paper offers unique insights to unpack the lived experiences of mountain people on climate change through articulation by exploring anecdotal narratives that have been produced by them through their attachment with land. This paper is based on ethnographic study conducted of the Nhāson Valley, Manang from 2012 to 2022. Informal conversations with local people, the documentation of native terms, and the interpretation of cultural meanings associated with these terms and phrases are the sources of data used to understand climate change in the valley. The exploration of the meanings associated with anecdotal narratives provide holistic insights into the relationship between society and environment, as well as the historical and contextual understanding of the climate change taking place in the place-specific locality, indigenous worldview of environmental change, lived experiences of changes in climatic variables rather than models produced by modern sciences. It offers a distinct and alternative ontology than mainstream approach in understanding the impacts of climate change in the local cultural context.